2013
DOI: 10.1371/journal.pone.0057338
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional Profiling Provides Insights into the Evolution and Development of the Zygomorphic Flower of Vicia sativa (Papilionoideae)

Abstract: Background Vicia sativa (the common vetch) possesses a predominant zygomorphic flower and belongs to the subfamily Papilionoideae, which is related to Arabidopsis thaliana in the eurosid II clade of the core eudicots. Each vetch flower consists of 21 concentrically arranged organs: the outermost five sepals, then five petals and ten stamens, and a single carpel in the center.Methodology/Principal Findings We explored the floral transcriptome to examine a genome-scale genetic model of the zygomorphic flower of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 73 publications
4
28
0
Order By: Relevance
“…Our GO enrichment analysis showed that unigenes related to the category "transcription" were significantly enriched. This finding agreed with our previous investigations on alfalfa and Vicia sativa using similar GO analyses of SSR-containing unigene approaches (Liu et al, 2013a;Liu et al, 2013b). The results of GO enrichment analysis of unigenes containing EST-SSR loci indicated that EST-SSR loci are not randomly distributed in the transcriptome and it preference exists in transcription factors (Fig S5C).…”
Section: Discussionsupporting
confidence: 92%
“…Our GO enrichment analysis showed that unigenes related to the category "transcription" were significantly enriched. This finding agreed with our previous investigations on alfalfa and Vicia sativa using similar GO analyses of SSR-containing unigene approaches (Liu et al, 2013a;Liu et al, 2013b). The results of GO enrichment analysis of unigenes containing EST-SSR loci indicated that EST-SSR loci are not randomly distributed in the transcriptome and it preference exists in transcription factors (Fig S5C).…”
Section: Discussionsupporting
confidence: 92%
“…Our GO enrichment analysis showed that unigenes related to the category "transcription" were significantly enriched. This finding agreed with our previous investigations on alfalfa and Vicia sativa using similar GO analyses of SSR-containing unigene approaches (Liu et al, 2013a;Liu et al, 2013b) and indicated that the "transcription"-related unigenes are likely to contain more SSR repeats than other unigenes (Luo et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…As a convenient tool for transcriptome analysis, RNA-Seq, has been increasingly targeted at species that do not have access to genomic sequences [53][54][55]. Here, we used RNA-Seq to measure gene expression levels in non-heading Chinese cabbage different varieties and under low temperature treatment.…”
Section: Discussionmentioning
confidence: 99%